Studies on the prevalence and biology of Blastocystis spp. isolated from zoonotic reservoirs in Malaysia / Farah Haziqah Meor Termizi - Farah Haziqah, Meor Termizi (2017)
Blastocystis is a highly prevalent protozoan parasite of the intestinal tract of a wide range of animal hosts, including humans. To date, very little information is available of parasite in zoonotic potential reservoirs namely, companion animals, household pests and poultry population. The suggestion that the intimate association between humans and animals could facilitate transmission led us to investigate Blastocystis in several animal hosts in the domestic environment such as cats, dogs, rodents, cockroaches, house geckos and chickens as no data is available to date. From October 2012 until April 2015, a total of 938 intestinal contents and/or faecal samples from different hosts were collected from three states of Peninsular Malaysia namely; Kuala Lumpur, Selangor and Perak. The prevalence of Blastocystis infection was investigated by screening and in vitro cultivation method using Jones medium supplemented with 10% horse serum. A total of 26.3% (47/179) chicken faecal samples screened were positive for Blastocystis infection with high prevalence in free-range species compared to barnreared chicken. Results from this first epidemiological study showed positive infection in broiler chicken despite reared in farming method least prone to contamination. Intestinal infections were equally high 45.4% (133/293) in wild rats and cockroaches 40.4% (61/151) particularly the nymph stage. All infections were observed asymptomatic. Surprisingly, house geckos were free from infection. Light microscopy examination between the animal isolates was almost similar in morphology to B. hominis with the exception for their considerable size variations (chicken isolates: 10 to 100 μm; wild rat isolate: 4 to 45 μm; cockroach isolate 9 to 15 μm in diameter). Furthermore, ultrastructure examination demonstrated surface coat thickness and electron density also varied between different isolates. Close to half of the chicken isolates were completely electron-lucent when examined under the transmission electron micrographs whereas electron dense areas were observed in the central vacuole of the wild rat and cockroach isolate which indicated lipid accumulation. Surface coat were present on all isolates with the cockroach isolates the thickest between 276.17 to 336.67 nm followed by chicken isolates (239.39 to 169.27 nm) and the least in wild rat isolates (135.51 to 196.82 nm). Using the sequenced-tagged site (STS) primers and DNA barcoding method, four subtypes were detected from chicken isolates namely, ST1, ST6, ST7 and ST8. Meanwhile, four subtypes were detected from wild rats with ST1, ST4, ST5 and ST7. In cockroach population, two cockroach isolates were identified as ST3 and one isolate was closely related to allele 114 which is most likely to be the new subtype. Although cultivation was unsuccessful from all cat and dog samples, 12 cat samples were found positive for Blastocystis sp. ST1. The finding of this study adds to our understanding of the biology, transmission as well as distribution of this organism in animals living in close association to humans and highlights their zoonotic potential.